Myocardial Expression of Estrogen Receptor-mRNA Is Associated With Lower Markers of Post-operative Organ Damage in Young Patients With Congenital Cardiac Defect - Rouatbi, Hatem; Farhat, Nesrine; Heying, Ruth; Vazquez-Jimenez, Jaime F.; Parent, Anne-Simone; Seghaye, Marie-Christine (Frontiers in Pediatrics, 2021)
Background: Estrogen receptors (ERs) relate to cardio-protection in adults, but their role in younger patients is not known. We aimed to assess the myocardial expression of ERα- and ERβ- mRNA in young patients with congenital cardiac disease and to analyze their putative protective role. Patients and Methods: Twenty children and young adults (seven females and 13 males) with a median age of 13.8 years (interquartile range: 12.3 years) were enrolled in this prospective study. The myocardial expression of ER-mRNA and genes involved in inflammation, growth, and stress response was assessed by real-time PCR and was correlated to post-operative (po) outcome. Results: ER-mRNA was detected in the myocardium of all patients, independently of gender and age. The expression of ER-mRNA correlated with that of mRNA coding for brain natriuretic peptide and for all cytokines tested. A higher ERα-mRNA expression correlated with lower troponin T concentrations at 24 h po (p = 0.032), higher PaO2/FiO2 ratio at 4 h po (p = 0.059), lower fluid retention at 4 h po (p = 0.048), and lower aspartate aminotransferase (AST) levels at 24 h po (p = 0.047). A higher ERβ-mRNA expression was also correlated with lower fluid retention at 24 h po (p = 0.048). Patients in whom the levels of ERα- and ERβ-mRNA were >P50 had lower troponin T (p = 0.003, respectively) and lower AST concentrations at 24 h po (p = 0.043, respectively) than the others. Conclusions: The expression of ERα- and ERβ-mRNA is present in the myocardium of children and young adults with congenital cardiac defect and is associated with lower markers of po organ damage. This suggests that ERs may provide perioperative organ protection in this population.